The experience of participation: eliciting the views of children on the autism spectrum. Issue 9 (24th April 2022) - Simpson, Kate; Imms, Christine; Keen, Deb
Abstract: Purpose: Children on the autism spectrum are reported to participate less in leisure activities than their peers. Little is known about what participation means for this group and the child's voice has been largely absent, partly due to methodological limitations. To address this limitation, alternative methods of eliciting children's perspectives are needed. The aim of this study is to elicit children's views about their participation experiences using a multi-method approach, and children's feedback on the method. Methods: Four children on the autism spectrum (9–13 years) used a video recording device to collect data over a 1-week period on their participation in activities. The children recorded an in-the-moment narrative to describe the activity and their in-the-moment experiences. A follow-up individualised interview was conducted, allowing children to present their unique views on their activity participation and feedback. Results: The children's differing perspectives identified participation as a transactional and dynamic process. Involvement was described as an individual and subjective experience, with participation influenced by personal, social, and physical factors. Children viewed the research experience positively. Recording while participating "in-the-moment" was challenging. Conclusion: The first-person perspective provided unique insights into the children's participation experiences. This approach has the potential to inform methodological practices. IMPLICATIONS FOR REHABILITATION: Children can describe their experience of participation and identify internal and external factors that influence their participation. Participation is a transactional and dynamic process. Video provides a useful method for children to record their "in the moment" experiences. Children's video recordings provide a stimulus for interview discussions in both research and clinical practice.